Circulating MicroRNAs as Minimally Invasive Biomarkers for Cancer Theragnosis and Prognosis - Cho, William C. (Frontiers in Genetics, 2011)
Novel cancer biomarker discovery is urgently needed for cancer theragnosis and prognosis, and among the many possible types of samples, blood is regarded to be ideal for this discovery as it can be collected easily in a minimally invasive manner. Results of the last few years have ascertained the quantification of microRNA (miRNA) as a promising approach for the detection and prognostication of cancer. Indeed, an increasing number of studies have shown that circulating cancer-associated miRNAs are readily measured in plasma or serum and they can robustly discriminate cancer patients from healthy controls, as well as distinguishing between good-prognosis and poor-prognosis patients. Furthermore, recent findings also suggest the potential of circulating miRNAs in the screening, monitoring, and treatment of cancer. This article summarizes the most significant and latest discoveries of original researches on circulating miRNAs involvement in cancer, focusing on the potential of circulating miRNAs as minimally invasive biomarkers for cancer theragnosis and prognosis.